Mixed-method heat acclimation induces heat adaptations in international triathletes without training modification - James, C. A.; Willmott, A. G. B.; Lee, C: W. D.; Pun, T. K. G.; Tai, R.; Gibson, O. R. (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships.